Production of infectious HCV genotype 1b virus in cell culture using a novel Set of adaptive mutations. Issue 1 (December 2016) - Mori, Ken-ichi; Matsumoto, Akihiro; Maki, Noboru; Ichikawa, Yuki; Tanaka, Eiji; Yagi, Shintaro
Abstract Background Despite the high prevalence of genotype 1b hepatitis C virus (HCV) among patients, a cell culture system that permits entire viral life cycle of genotype 1b isolates is limited. To develop a cell-cultured hepatitis C virus (HCVcc) of genotype 1b, the proper combination of HCV genomic variants and host cells is essential. HCV genomes isolated from patients with distinctive symptoms may provide the variants required to establish an HCVcc of genotype 1b. Results We first established subgenomic replicons in Huh7 cells using HCV cDNAs isolated from two patients: one with fulminant hepatitis after liver transplantation (TPF1) and another with acute hepatitis and moderate symptoms (sAH). Replicons established from TPF1 and sAH showed mutations in NS4B and in NS3 and NS5A, respectively. Using these replication machineries, we constructed HCV genomic RNAs for each isolate. Virus infectivity was evaluated by a focus-forming assay, which is dependent on the intracellular expression of core antigen, and production of virus particles was assessed by density-gradient centrifugation. Infectious virus was only observed in the culture medium of cells transfected with TFP1 HCV RNA. A chimeric genome with the structural segment (5′-untranslated region [UTR] through NS2) from sAH and the replication machinery (NS3 through 3′-UTR) from TPF1 exhibited greater infectivity than did TFP1, despite formation of deficient virus particles in sAH, suggesting that this genomic segment potentiates virus particle formation. To identify the responsible variants, infectious virus formation was assessed in a chimeric genome carrying parts of the sAH structural segment of the TPF1 genome. A variant in NS2 (M170T) was identified that enhanced infectious virus formation. HCVcc carrying an NS2 gene encoding the M170T substitution and adaptive mutations in NS4B (referred to as TPF1-M170T) infected naïve cured Huh7 cells in a CD81-dependent manner. Conclusions We established a novel HCVcc of genotype 1b in Huh7 cells by introducing an amino acid variant in NS2 and adaptive mutations in NS4B from HCV genomic RNA isolated from a patient with fulminant HCV after liver transplantation.